Dementia risk estimation in persons at risk and the predictive turn in Alzheimer’s disease—The PreTAD project: Study protocol with an ethical, clinical, linguistic, and legal approach - Michelle Gerards; Annika Baumeister; Constanze Hübner; Federica Ribaldi; Yahveth Cantero-Fortiz; Julia Braun; Mercè Boada; Giovanni B. Frisoni; Frank Jessen; Björn Schmitz-Luhn; Carolin Schwegler; Christiane Woopen; et al. (PLoS ONE, 2025)
Background Despite progress in the field of Alzheimer’s disease (AD) dementia risk estimation, little is known about its impact at the individual and societal levels. Objective Introducing the explorative tri-national PreTAD project (The Predictive Turn in Alzheimer’s Disease: Ethical, Clinical, Linguistic and Legal Aspects), which aims to (1) learn about attitudes, needs, and perspectives on AD dementia risk estimation of the general population and cognitively unimpaired individuals with and without contact to memory clinics, (2) identify anticipated impacts of AD dementia risk estimation and (3) discuss the implications of the paradigm shift in medicine at individual and societal levels from an ethical, linguistic and legal perspective. Methods Different approaches are used: (1) an assessment of a population without experience with dementia, (2) an assessment in memory clinics, and (3) an online survey of the general population. Participants include cognitively healthy adults (n=2760), first-degree relatives of dementia patients (n=150), and participants with existing (n=150) and newly diagnosed (n=90) subjective cognitive decline (SCD) from Germany, Switzerland, and Spain. Results As part of the PreTAD project, new questionnaires are developed that (1) collect attitudes, needs, and perspectives on AD dementia risk estimation and (2) assess anticipated impacts of dementia risk estimation using hypothetical blood-based biomarker dementia risk scenarios. Conclusion The PreTAD study combines an interdisciplinary approach to develop a framework for predictive medicine in the preclinical stages of AD and supports improving communication of biomarker-based dementia risk estimation in clinical practice. The study was registered in the German Clinical Trials Register (DRKS00029035 on 03/08/2023). Trial registration German clinical trials register (Deutsches Register Klinischer Studien, DRKS): http://www.drks.de/DRKS00029035, DRKS registration number: DRKS00029035, date of registration: 08.03.2023. Protocol version 3.0, date 01.06.2024